Composition and structure of a mucilaginous polysaccharide extracted from black gram (Vigna mungo (L.) Hepper) during preparation of fermented dairy alternatives - Ian M. Sims; Susie M. Carnachan; Meg Macgregor-Dunn; Yiran Wang; Alejandra Acevedo-Fani; Harjinder Singh; Ulrike Hubl; Debashree Roy; Arup Nag (Food Hydrocolloids, 2026)

Structural characterisation of a fucose-rich acidic extracellular polysaccharide produced by Lindavia intermedia in New Zealand lakes - Cara A. Luiten; Ian M. Sims; Tracey J. Bell; Peter T. Northcote; A. Jonathan Singh; Andrew R. Lewis; Guilherme L. Sassaki; Phil M. Novis; Marc Schallenberg; Simon F.R. Hinkley (Algal Research, 2026)

Characterisation of novel polysaccharide extracts from indigenous New Zealand ferns - Felicia Zhi Wen Peh; Kelvin K.T. Goh; Cara A. Luiten; Ian M. Sims; Lara Matia-Merino (Food Hydrocolloids, 2026)

Isolation and characterisation of cell wall polysaccharides from taewa (Māori potatoes; Solanum tuberosum L.) - Cara.A. Luiten; Simon F.R. Hinkley; Nick R. Roskruge; Saii A. Semese; Anne-Louise M. Heath; Tracy L. Perry; Nancy J. Rehrer; Ian M. Sims (Food Hydrocolloids, 2026)

Factor analysis of multimodal MRI, biofluid, and vascular biomarkers reveals latent constructs of brain health - Ella Rowsthorn; Ming Ann Sim; William T. O’Brien; Stuart J. McDonald; Katherine Franks; Benjamin Sinclair; Trevor T.-J. Chong; Stephanie Yiallourou; Marina Cavuoto; Lucy Vivash; Terence J. O’Brien; Xingfeng Shao; et al. (GeroScience, 2025)
Individual imaging and fluid biomarkers provide insights into specific components of brain health, but integrated multimodal approaches are necessary to capture the complex, interrelated biological systems that contribute to brain homeostasis and neurodegenerative disease. Using data from the Brain and Cognitive Health (BACH) cohort study ( N = 127; mean age = 67 years, 68% women), we performed an exploratory factor analysis to identify latent constructs of brain health. We included multimodal neurovascular imaging markers, brain atrophy metrics, plasma Alzheimer’s disease (AD) biomarkers, and cardiovascular risk factors. Five constructs emerged: “Brain & Vascular Health” (greater hippocampal volume, basal ganglia enlarged perivascular spaces (ePVS), cerebral blood flow, and HDL cholesterol; lower ventricle volume and BMI), “Structural Integrity” (greater cortical thickness, fractional anisotropy, and basal ganglia ePVS), “White Matter (WM) Fluid Dysregulation” (greater WM ePVS and Free Water), “AD Biomarkers” (higher phosphorylated tau [pTau]181 and pTau217; lower amyloid-beta 42/40 ratio), and “Neuronal Injury” (higher glial fibrillary acidic protein and neurofilament light chain). All constructs were associated with age (β = - 0.70–0.39, p ≤ 0.014), except for WM Fluid Dysregulation ( p > 0.05). Brain and Vascular Health and Structural Integrity (partial r = 0.305, p < 0.001) and AD biomarkers and neuronal injury (partial r = 0.248, p = 0.005) were positively correlated. Only Brain and Vascular Health was associated with global cognition (β = 0.27, SE = 0.13, p = 0.043). These findings provide a data-driven framework for examining distinct constructs underlying vascular health, fluid regulation, and neurodegenerative pathology. We demonstrate the utility of using multiple biomarkers to probe these biological systems, paving the way for future research to explore how these systems change across diverse neurodegenerative conditions. Graphical abstract

Ulvans are not equal - Linkage and substitution patterns in ulvan polysaccharides differ with Ulva morphology - Joel T. Kidgell; Christopher R.K. Glasson; Marie Magnusson; Ian M. Sims; Simon F.R. Hinkley; Rocky de Nys; Susan M. Carnachan (Carbohydrate Polymers, 2024)

Cover crops in cereal rotations: A quantitative review - Marco Fioratti Junod; Brian Reid; Ian Sims; Anthony J. Miller (Soil and Tillage Research, 2024)

Does harvesting age matter? Changes in structure and rheology of a shear-thickening polysaccharide from Cyathea medullaris as a function of age - Akshay Bisht; Kelvin K.T. Goh; Ian M. Sims; Patrick J.B. Edwards; Lara Matia-Merino (Carbohydrate Polymers, 2024)

Fractionation and characterisation of pectin-rich extracts from garlic biomass - Piyachat Sunanta; Sarana Rose Sommano; Cara A. Luiten; Mahdieh Ghofrani; Ian M. Sims; Tracey J. Bell; Susan M. Carnachan; Simon F.R. Hinkley; Vassilis Kontogiorgos (Food Chemistry, 2024)

Below-ground pitfall traps for standardised monitoring of soil mesofauna: Design and comparison to Berlese/Tullgren funnels - Marco Fioratti Junod; Brian J. Reid; Ian Sims; Anthony J. Miller (Pedobiologia, 2023)

Shear and temperature sensitivity of a shear-thickening biopolymer from the New Zealand black tree fern - Akshay Bisht; Kelvin K.T. Goh; Ian M. Sims; Patrick J.B. Edwards; Lara Matia-Merino (Food Hydrocolloids, 2023)

Novel 4-O-β-d-xylopyranosyl-3,6-anhydro-l-galactopyranosyl disaccharide units in a polysaccharide from the red alga Pyrophyllon subtumens - Ruth Falshaw; Richard H. Furneaux; Ian M. Sims; Simon F.R. Hinkley; Joel T. Kidgell; Tracey J. Bell (Carbohydrate Polymers, 2023)

The importance of including habitat-specific behaviour in models of butterfly movement - Luke C. Evans; Richard M. Sibly; Pernille Thorbek; Ian Sims; Tom H. Oliver; Richard J. Walters (Oecologia, 2020)
Dispersal is a key process affecting population persistence and major factors affecting dispersal rates are the amounts, connectedness and properties of habitats in landscapes. We present new data on the butterfly Maniola jurtina in flower-rich and flower-poor habitats that demonstrates how movement and behaviour differ between sexes and habitat types, and how this effects consequent dispersal rates. Females had higher flight speeds than males, but their total time in flight was four times less. The effect of habitat type was strong for both sexes, flight speeds were ~ 2.5 × and ~ 1.7 × faster on resource-poor habitats for males and females, respectively, and flights were approximately 50% longer. With few exceptions females oviposited in the mown grass habitat, likely because growing grass offers better food for emerging caterpillars, but they foraged in the resource-rich habitat. It seems that females faced a trade-off between ovipositing without foraging in the mown grass or foraging without ovipositing where flowers were abundant. We show that taking account of habitat-dependent differences in activity, here categorised as flight or non-flight, is crucial to obtaining good fits of an individual-based model to observed movement. An important implication of this finding is that incorporating habitat-specific activity budgets is likely necessary for predicting longer-term dispersal in heterogeneous habitats, as habitat-specific behaviour substantially influences the mean (> 30% difference) and kurtosis (1.4 × difference) of dispersal kernels. The presented IBMs provide a simple method to explicitly incorporate known activity and movement rates when predicting dispersal in changing and heterogeneous landscapes.

Animal-Borne Telemetry: An Integral Component of the Ocean Observing Toolkit - Rob Harcourt; Ana M. M. Sequeira; Xuelei Zhang; Fabien Roquet; Kosei Komatsu; Michelle Heupel; Clive McMahon; Fred Whoriskey; Mark Meekan; Gemma Carroll; Stephanie Brodie; Colin Simpfendorfer; et al. (Frontiers in Marine Science, 2019)

The use of historical environmental monitoring data to test predictions on cross-scale ecological responses to alterations in river flows - Matthew J. Colloff; Ian C. Overton; Brent L. Henderson; Jane Roberts; Julian R. W. Reid; Roderick L. Oliver; Anthony D. Arthur; Tanya M. Doody; Neil C. Sims; Qifeng Ye; Susan M. Cuddy (Aquatic Ecology, 2018)

Warming-Induced Shrub Expansion and Lichen Decline in the Western Canadian Arctic - Robert H. Fraser; Trevor C. Lantz; Ian Olthof; Steven V. Kokelj; Richard A. Sims (Ecosystems, 2014)

Biomonitoring seasonal changes in the environmental impact of atmospheric pollution around junction 16 of the M25 London Orbital Motorway (a high traffic area), United Kingdom - Ian Sims; Mark Crane; Ian Johnson; Peter Credland (Ecotoxicology, 2011)

Biomonitoring the environmental impact of atmospheric emissions from the Avonmouth zinc smelter, United Kingdom - Ian Sims; Mark Crane; Ian Johnson; Peter Credland (Ecotoxicology, 2009)

Genetic mapping of a major gene affecting onion bulb fructan content - John McCallum; Andrew Clarke; Meeghan Pither-Joyce; Martin Shaw; Ruth Butler; Don Brash; John Scheffer; Ian Sims; Sjaak van Heusden; Masayoshi Shigyo; Michael J. Havey (Theoretical and Applied Genetics, 2006)

Comparison of the Effects of Wet N Deposition (NH4Cl) and Dry N Deposition (NH3) on UK Moorland Species - Ian D. Leith; Lucy J. Sheppard; Carole E.R. Pitcairn; J. Neil Cape; Paul W. Hill; Valerie H. Kennedy; Y. Sim Tang; Ron I. Smith; David Fowler (Water, Air, & Soil Pollution, 2001)

Isolation and characterization of cell walls from the mesocarp of mature grape berries ( Vitis vinifera ) - Kylie J. Nunan; Ian M. Sims; Antony Bacic; Simon P. Robinson; Geoffrey B. Fincher (Planta, 1997)

Isolation and characterization of cell walls from the mesocarp of mature grape berries (Vitis vinifera) - Kylie J. Nunan; Ian M. Sims; Antony Bacic; Simon P. Robinson; Geoffrey B. Fincher (Planta, 1997)